1988
DOI: 10.1136/oem.45.8.532
|View full text |Cite
|
Sign up to set email alerts
|

Indirect estimation of maximal oxygen uptake for study of working populations.

Abstract: A total of 345 shipyard workers (aged 23 to 47) volunteered to perform progressive exercise on a cycle ergometer (15 W/min increments) up to the symptom limited maximum. The results were used to obtain maximal oxygen uptake (iO2 max), the oxygen uptake at a respiratory exchange ratio of unity (0O2 at R1.0), and cardiac frequency at an oxygen uptake of 45 mmol/min (fC45). In this group 156 men (45% of initial population) attained tO2 max as defined, 108 (31%) withdrew or did not exercise maximally, and 49 (14%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…The 95 % tolerance limits of individual changes amounted to + 7 beats min-1 and represented a 4 6 % variability. These results showed that the variability attending the measurement of the three indices was small, and was consistent with their previously reported accuracy (Kappagoda et al 1979;Weller et al 1985Weller et al , 1988.…”
Section: First Trialsupporting
confidence: 92%
See 2 more Smart Citations
“…The 95 % tolerance limits of individual changes amounted to + 7 beats min-1 and represented a 4 6 % variability. These results showed that the variability attending the measurement of the three indices was small, and was consistent with their previously reported accuracy (Kappagoda et al 1979;Weller et al 1985Weller et al , 1988.…”
Section: First Trialsupporting
confidence: 92%
“…The most recent of these has been based non-invasively on the measurements of VO at a respiratory exchange ratio of unity (R. 1). This VO /R=1 index can be readily estimated with adequate reproducibility, and, because it correlated with anaerobic threshold it can provide an indicator of capacity for prolonged work (Weller et al 1985(Weller et al , 1988. In addition, the use of HR/ VO elevation or VO /R=1 value avoids the inaccuracy of extrapolations from submaximal exercise to predict maximal indices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first minute of exercise there was no externally applied load, thereafter the load was increased to 20 watts and incremented by 20 watts each minute. The exercise was terminated when the respiratory exchange ratio reached a value of unity (approximately 70% of maximal oxygen uptake, [12]). On completion of the exercise test, the subjects returned to the supine position and heart rate and blood pressure were monitored until recovery to pre-exercise resting levels.…”
Section: Methodsmentioning
confidence: 99%
“…Habitual physical activity was rated on a four point scale going from (1) inactive, (2) occasional exercise, (3) regular but non-competitive sport, and (4) participation in competitive sport. 5 Subjects then attended the laboratory for measurement of ventilatory capacity by dynamic spirometry, carbon monoxide transfer factor ofthe lung by the single breath method, and the physiological response to progressive submaximal exercise on a cycle ergometer. A self administered questionnaire scoring anxiety and depression and a semantic differential assessing the subjects's attitudes and beliefs regarding his health were completed.…”
Section: Subjectsmentioning
confidence: 99%